Predictive value of myositis antibodies: role of semiquantitative classification and positivity for more than one autoantibody - Anne M Kerola; Arno Hänninen; Annukka Pietikäinen; Julia Barantseva; Annaleena Pajander (RMD Open)
Objectives We assessed the positive predictive value (PPV) of 17 myositis antibodies for having a diagnosis of myositis and other myositis-spectrum conditions (interstitial lung disease (ILD), connective tissue diseases (CTD), malignancy) and evaluated the impact of semiquantitative classification and antibody overlap on the PPVs.Materials and methods We retrospectively identified 1068 individuals ≥18 years who tested positive for ≥1 antibody in the EUROLINE myositis line blot assay or positive for anti-3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) in an ELISA-based test between 2015 and 2020 in 15 out of the 20 hospital districts in Finland. We extracted clinical diagnoses from the Care Register for Health Care between January 2013 and June 2022.Results The PPV for a myositis diagnosis (ever during data collection) was highest for anti-HMGCR antibodies (94%), followed by anti-MDA5, anti-Jo-1 and anti-TIF1-γ (49–54%). Regarding other myositis antibodies, 18–42% of cases had myositis. Anti-synthetase antibodies, anti-MDA5, anti-PM-Scl100, anti-SAE1 and anti-Ro52 had a PPV for ILD of 25–47%. A PPV for CTD was highest for anti-Ro52 (57%). The PPV for malignancy was highest for anti-TIF1-γ (38%), followed by anti-PL-7 (32%). Stronger antibody band intensity was associated with higher PPVs for myositis and CTD but not for ILD or malignancies. Simultaneous positivity for ≥2 antibodies compared with single antibody was associated with higher PPVs for myositis, CTD and ILD.Conclusion The PPV of myositis antibodies for diagnoses of myositis or other myositis spectrum diseases vary considerably between individual autoantibodies. Higher PPVs can be expected with stronger band intensities and with the presence of ≥2 overlapping myositis antibodies.